The analysis of factors influencing literacy and numeracy skills of biology education students at universitas lancang kuning - Ramadansur, Rahmat; In’am, Akhsanul; Pantiwati , Yuni; Baiduri , Baiduri (JURNAL BIOEDUKATIKA, 2025)
This study aims to analyze the factors affecting biology education students' literacy and numeracy skills, focusing on the influence of previous education quality, learning motivation, social environmental support, and learning facilities. The study employs a descriptive approach with Confirmatory Factor Analysis. The respondents' achievement level for the Previous Education Quality variable (X1) was moderate (76.22%). The Learning Motivation variable (X2) had a Total Correct Rate (TCR) of 84.04%, which falls under the good category. The Social Environmental Support variable (X3) scored 58.63%, categorized as poor. The Learning Facilities variable (X4) obtained a TCR of 55.39%, also in the poor category. After conducting the confirmatory factor analysis, two factors were identified, explaining 60.47% of the variance from the original variables, with the remaining 39.53% explained by other unexamined variables in this study. With a better understanding of these factors, it is hoped that this research can provide strategic recommendations for higher education institutions in developing curricula, learning methods, and learning environments that can effectively improve students' numeracy and literacy skills in the field of biology.